2009
DOI: 10.1016/j.ajic.2009.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term control of hospital-wide, endemic multidrug-resistant Acinetobacter baumannii through a comprehensive “bundle” approach

Abstract: Background-Acinetobacter baumannii (Ab) is emerging as a multidrug-resistant (MDR) nosocomial pathogen of considerable clinical importance. Data on the efficacy of infection control measures in endemic situations are lacking. Here, we investigated the impact of a long-term multifaceted "bundle" approach in controlling endemic MDR Ab in a 950-bed tertiary care center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 35 publications
2
64
0
Order By: Relevance
“…The real-time assay was negative when genomic DNA from clinical isolates of Pseudomonas aeruginosa, Klebsiella pneumoniae, Moraxella catarrhalis, and Escherichia coli was used in the assay. Taken together, these results indicate that the ompA real-time assay is sensitive and specific for detecting and quantifying A. baumannii genomic DNA.Results from environmental samples in the ICUs demonstrated that A. baumannii was identified on 39% of surfaces using bacterial culture (Table 1), a prevalence similar to those of previous reports describing the presence of A. baumannii on environmental surfaces in intensive care settings in which this species is endemic (1,8). Duplicate samples tested using real-time PCR showed the presence of A. baumannii on 77% of surfaces, a significantly higher level than the results obtained with bacterial culture (P Ͻ 0.0001 by chi-squared test).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…The real-time assay was negative when genomic DNA from clinical isolates of Pseudomonas aeruginosa, Klebsiella pneumoniae, Moraxella catarrhalis, and Escherichia coli was used in the assay. Taken together, these results indicate that the ompA real-time assay is sensitive and specific for detecting and quantifying A. baumannii genomic DNA.Results from environmental samples in the ICUs demonstrated that A. baumannii was identified on 39% of surfaces using bacterial culture (Table 1), a prevalence similar to those of previous reports describing the presence of A. baumannii on environmental surfaces in intensive care settings in which this species is endemic (1,8). Duplicate samples tested using real-time PCR showed the presence of A. baumannii on 77% of surfaces, a significantly higher level than the results obtained with bacterial culture (P Ͻ 0.0001 by chi-squared test).…”
supporting
confidence: 76%
“…In this context, patients are exposed to A. baumannii via contact with contaminated hospital equipment or by contact with hospital personnel carrying the bacteria. A number of studies have demonstrated widespread contamination with A. baumannii on hospital environmental surfaces, most notably in intensive care units (ICUs) (1,4,8,9).Environmental surveillance protocols have been employed for the identification of hospital equipment colonized by A. baumannii so that appropriate decontamination procedures can be carried out (1,4,8,9). Since these surveillance methods employ conventional bacterial culture to determine the presence of A. baumannii, definitive species identification can require between 24 and 48 h. Nucleic acid-based tests, such as real-time PCR, have been employed for the identification of numerous bacterial pathogens (2); however, to our knowledge this technique has not been applied to identifying contaminated hospital equipment.…”
mentioning
confidence: 99%
“…7 Other nosocomial infections, such as Acinetobacter baumanii, present rates of infection more similar to those found for rotavirus in this study (0.82 cases per 100 admissions). 12 When comparing local studies performed in other WHO European Region countries, significant variation in nosocomial rotavirus incidence rate can be found, from 1% of all admissions in Israel or 1.9% in Italy to 13.9% in France. 6,11,13 In other countries, published rotavirus incidence rates range from 0.03 per 100 admissions in Australia to 2 per 100 admissions in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were collected from patient beds, bedside tables, alcohol-based hand rub dispensers, IV poles, bedside chairs, equipment carts, infusion pumps, patient records, doorknobs, keyboards, storage cabinets, nurses' stations, sinks, light switches, heating vents, ambu-bags, dialysis units, telephones, and ultrasound equipment. After sample collection, swabs were placed in 1 ml of Luria-Bertani broth and incubated at 37°C for 24 h with shaking at 220 rpm, as incubation of samples in nonselective media has been shown to be effective for isolation of A. baumannii (1,6). One hundred microliters of the enrichment culture was spread on LAM plates (Hardy Diagnostics, CA) and incubated for 16 h at 37°C.…”
mentioning
confidence: 99%
“…Environmental surveillance of hospital surfaces is useful in determining if equipment is colonized by A. baumannii and identifying the sources of hospital outbreaks (3,5,6). Leeds Acinetobacter medium (LAM) is a differential medium developed to selectively support the growth of Acinetobacter species (4).…”
mentioning
confidence: 99%